(untitled) - Biggs, Barton (Hoboken, N.J., 2006)
Rare is the opportunity to chat with a legendary financial figure and hear the unvarnished truth about what really goes on behind the scenes. Hedgehogging represents just such an opportunity, allowing you to step inside the world of Wall Street with Barton Biggs as he discusses investing in general, hedge funds in particular, and how he has learned to find and profit from the best moneymaking opportunities in an eat-what-you-kill, cutthroat investment world.
Keywords: Hedge funds